2012
DOI: 10.1890/es12-00266.1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat corridors alter relative trophic position of fire ants

Abstract: Abstract. Habitat fragmentation disrupts species movement, leading to local extinctions and altered community structure. Habitat corridors, which connect isolated patches of habitat and facilitate movement between patches, provide a potential solution to these negative impacts. However, most studies to date have examined the movement of species alone without considering emergent effects on the community (e.g., altered trophic structure). We use large-scale, experimental landscapes and nitrogen stable isotopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Resasco et al. () reported similar patterns, namely that the trophic position of omnivorous ants increased with plant richness. This implies that shifts in omnivore feeding behavior can contribute to higher predation rates with increasing plant diversity.…”
Section: Discussionmentioning
confidence: 75%
“…Resasco et al. () reported similar patterns, namely that the trophic position of omnivorous ants increased with plant richness. This implies that shifts in omnivore feeding behavior can contribute to higher predation rates with increasing plant diversity.…”
Section: Discussionmentioning
confidence: 75%
“…Trophic position can be used as an indicator for the dependence of ants on the exudates of hemipterans, with a lower trophic position indicating a tighter relationship (Davidson et al 2003, Wilder et al 2011b. Several recent studies have found that habitat type, ecological corridor, logging, and species invasion can lead to shifts in trophic position for ants (Gibb and Cunningham 2011, Wilder et al 2011b, Resasco et al 2012, Woodcock et al 2013). However, the shifts in trophic position and corresponding ecological effects of ants along environmental gradients have not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if disturbances affect resource abundance and composition, then consumers may alter their feeding through frequency-dependent prey switching or may truncate or expand their diet breadth based on the availability of their preferred prey (Jaworski, Bompard, Genies, Amiens-Desneux, & Desneux, 2013;Murdoch, 1969;Resasco, Levey, & Damschen, 2012). For example, if disturbances affect resource abundance and composition, then consumers may alter their feeding through frequency-dependent prey switching or may truncate or expand their diet breadth based on the availability of their preferred prey (Jaworski, Bompard, Genies, Amiens-Desneux, & Desneux, 2013;Murdoch, 1969;Resasco, Levey, & Damschen, 2012).…”
mentioning
confidence: 99%